Coordination of differentiation rate and local patterning in compound‐leaf development. Issue 6 (1st January 2021) - Israeli, Alon; Ben‐Herzel, Ori; Burko, Yogev; Shwartz, Ido; Ben‐Gera, Hadas; Harpaz‐Saad, Smadar; Bar, Maya; Efroni, Idan; Ori, Naomi
Summary: The variability in leaf form in nature is immense. Leaf patterning occurs by differential growth, taking place during a limited window of morphogenetic activity at the leaf marginal meristem. While many regulators have been implicated in the designation of the morphogenetic window and in leaf patterning, how these effectors interact to generate a particular form is still not well understood. We investigated the interaction among different effectors of tomato ( Solanum lycopersicum ) compound‐leaf development, using genetic and molecular analyses. Mutations in the tomato auxin response factor SlARF5/SlMP, which normally promotes leaflet formation, suppressed the increased leaf complexity of mutants with extended morphogenetic window. Impaired activity of the NAC/CUC transcription factor GOBLET (GOB), which specifies leaflet boundaries, also reduced leaf complexity in these backgrounds. Analysis of genetic interactions showed that the patterning factors SlMP, GOB and the MYB transcription factor LYRATE (LYR) coordinately regulate leaf patterning by modulating in parallel different aspects of leaflet formation and shaping. This work places an array of developmental regulators in a morphogenetic context. It reveals how organ‐level differentiation rate and local growth are coordinated to sculpture an organ. These concepts are applicable to the coordination of pattering and differentiation in other species and developmental processes.